ANALISIS PERAN GURU DAN DAMPAK PENGGUNAAN GAME ONLINE (MOBILE LEGENDS) UNTUK MENJAGA NILAI MORALETIKA SISWA SDN LAPATAMAN I - Mohammad Fahmi Syauqi; Ike Yuli Mestika Dewi; Syaiful Bahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of using the Mobile Legends online game on the development of students' moral and ethical values at LAPATAMAN I Elementary School. The methodology used is a qualitative field approach, with data collection through observation, interviews, and documentation studies. The results showed two main impacts of the Mobile Legends game. The positive impacts include the development of teamwork, communication and strategic thinking skills, which are beneficial in the context of learning and social life. In addition, the game strengthens social relationships between students who share similar interests. However, significant negative impacts were also found, such as the reliance on playing time that interferes with learning concentration, and increased frustration and anxiety when losing. This can interfere with students' emotional management and cause social segregation between students who play and those who do not. The role of teachers, especially homeroom teachers, is crucial in supervising playtime and guiding students in managing emotions. Good communication between teachers and parents is also needed to monitor students' gaming habits outside of school hours.